2014
DOI: 10.5812/ijem.15503
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin and Resistin Serum Levels in Normal-Weight and Obese Women With Polycystic Ovary Syndrome

Abstract: Background:Polycystic ovary syndrome (PCOS) is the most common endocrinopathy among women of reproductive age that is linked to insulin resistance and obesity. While studies have shown that plasma levels of resistin and visfatin increase with obesity, the association between PCOS and these markers has not been described well.Objectives:This case-control study aimed to compare the serum levels of visfatin and resistin in women with PCOS in comparison with the healthy controls matched for age and body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…The study by D _ Ikmen et al [23] was treated as multiple separate studies in our meta-analysis due to different BMI and age strategies, as were the studies of Tsouma et al [36], Farshchian et al [8] and Olszanecka-Glinianowicz et al [27]. Therefore, there were 22 studies included in this metaanalysis.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…The study by D _ Ikmen et al [23] was treated as multiple separate studies in our meta-analysis due to different BMI and age strategies, as were the studies of Tsouma et al [36], Farshchian et al [8] and Olszanecka-Glinianowicz et al [27]. Therefore, there were 22 studies included in this metaanalysis.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 97%
“…Among them, visfatin is an adipocytokine with insulin-like activity [8], and elevated plasma visfatin has been reported in patients with metabolic syndrome, especially in obese and T2DM patients [9][10][11][12]. Greater visfatin expression has been also found in cardiovascular diseases [13], inflammatory disorder [14] and a prognosis of cancer [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study of PCOS women and matched non-PCOS controls, both free testosterone and visfatin were independent predictors of FMD. [64][65][66][67][68][69][70] While numerous studies have attributed raised visfatin levels to elevated adiposity rather than diagnosis of PCOS per se, 58,59,66,[71][72][73] several other studies have demonstrated increased visfatin levels in women with PCOS when compared with BMI-matched controls. 60,67,68,70,[74][75][76][77][78][79] Furthermore, visfatin mRNA is upregulated in omental adipose tissue in women with PCOS and is closely correlated with BMI and IR.…”
Section: Visfatinmentioning
confidence: 99%
“…In the present study, serum resistin levels were higher in PCOS patients but there was no association in the levels between PCOS cases and controls. Previous studies have described high serum resistin levels in PCOS cases, but the association was not significant (28,30,31). On the other hand, some studies did not find higher serum resistin levels in PCOS women compared to healthy controls (31,32).…”
Section: Discussionmentioning
confidence: 87%